Phenolic compounds influence seed dormancy of palicourea rigida h.b.k. (rubiaceae), a medicinal plant of the brazilian savannah - Inácio, Marielle C. [UNESP]; Moraes, Rita Maria de; Mendonça, Patricia Calligioni de [UNESP]; Morel, Lucas J. F.; França, Suzelei de Castro; Bertoni, Bianca; Pereira, Ana Maria Soares [UNESP] (Scientific Research Publishing, 2013)
Palicourea rigida H.B.K. (Rubiaceae), a medicinal species commonly known as douradinha, has wide distribution across ecosystems in Central and South America. This species exhibits seed dormancy delaying germination until optimal conditions for seedling growth and development are in place. While dormancy ensures species survival, it also presents a technical problem for developing P. rigida’s plant production program. Thus, the objective of this study was to investigate if secondary metabolites present in seeds influence the seed dormancy of P. rigida. Mature fruits were harvested from the native habitat, in the savanna region of the State of Minas Gerais during February 2009, 2010 and 2011. The content of phenolic compounds in the seed of P. rigida was measured, and the allelopathic effects were assessed using the germination of lettuces as model to detect phytotoxicity. The P. rigida seeds geminated at rates varying between 7% and 31% with a Seed Germination Index (SGI) of 0.09. Data suggest that the phenolic compounds present in the seeds may be responsible for seed dormancy.
Keywords: Cerrado; Douradinha; Medicinal plant; Conservation